The effects of dietary soybean hulls, particle size, and diet form on nursery pig performance - D L Goehring; B W James; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 1,100 nursery pigs (PIC C-29 × 359, initially 15.0 lb BW) were used in a 42-d growth trial to determine the effects of increasing soybean hulls (10 or 20%) and soybean hull particle size (unground or ground) in nursery pig diets fed in both meal and pelleted forms. The average particle size of the unground and ground soybean hulls were 617 and 398 Î¼, respectively. Pens of pigs (5 barrows and 5 gilts) were balanced by initial BW and randomly allotted to 1 of 8 treatments with 11 replications per treatment. A 2-phase diet series was used with treatment diets fed from d 0 to 14 for Phase 1 and d 14 to 42 for Phase 2. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of 10 or 20% unground or finely ground soybean hulls with diets in pelleted or meal form. For individual phases and overall (d 0 to 42), no soybean hull × particle size × diet form or particle size × soybean hull interactions (P>0.37 and P>0.17, respectively) were observed; however, diet form × particle size interactions were observed for F/G and ADFI (P<0.05 and P<0.10, respectively). Grinding soybean hulls resulted in improved F/G and reduced ADFI when added to meal diets, but did not change F/G and had less effect on ADFI when added to pelleted diets. Diet form × particle size interactions (P<0.05) also were observed for caloric efficiency on an ME and NE basis. Grinding soybean hulls slightly improved caloric efficiency in meal diets but worsened NE and ME caloric efficiency in pelleted diets. There was also a tendency for a diet form × soybean hulls interaction (P<0.06) for ADFI and F/G. Increasing soybean hulls from 10 to 20% increased ADFI and worsened F/G in meal diets but resulted in slightly reduced ADFI and no changes to F/G when added to pelleted diets; furthermore, there were tendencies for diet form × soybean hulls interactions (P<0.06) on caloric efficiency on an ME and NE basis in which increasing soybean hulls from 10 to 20% improved caloric efficiency to a greater extent in pelleted diets than in meal diets.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Nursery pig; Particle size; Soybean hulls